The Effect of Perceived Quality and Perceived Value on Repurchase Intention in Consumers of Chicken Salto Products with Customer Satisfaction as a Mediation Variable in an Islamic Business Perspective (Study on Consumers of Salto Chicken Bandar Lampung) - Jihan Agustin; Siska Yuli Anita; Sania Nuraziza (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine how Perceived Quality and Perceived Value relate to Repurchase Intention, mediated by Customer Satisfaction, among consumers of chicken salto products. This study uses an exploratory method with a quantitative approach, with a sample size of 96 respondents and data analysis using Structural Equation Modelling (SEM) and Partial Least Square (PLS) analysis techniques. The findings of this study indicate a positive and significant effect on the relationship between Perceived Value and Repurchase Intention, Perceived Quality and Customer Satisfaction, Perceived Value and Customer Satisfaction, Customer Satisfaction and Repurchase Intention, Customer Satisfaction mediating the effect of Perceived Quality on Repurchase Intention, and Customer Satisfaction mediating the effect of Perceived Value on Repurchase Intention. Additionally, there are results that do not affect the relationship between Perceived Quality and Repurchase Intention.